2015
DOI: 10.1016/j.joca.2015.03.034
|View full text |Cite
|
Sign up to set email alerts
|

The Intensive Diet and Exercise for Arthritis (IDEA) trial: 18-month radiographic and MRI outcomes

Abstract: Despite the potent effects of weight loss in this study on symptoms as well as mechanistic outcomes (such as joint compressive force and markers of inflammation), there was no statistically significant difference between the three active interventions on the rate of structural progression either on X-ray or MRI over 18-months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 45 publications
6
66
2
Order By: Relevance
“…In addition, only participants in whom MR imaging could be performed were included in the OAI study; thus, participants who had issues with fitting into the MR imaging surgery). Yet, the only statistical trend found in the previous assessment of structural knee abnormalities and different types of weight loss (exercise, diet, and diet combined with exercise) was a beneficial effect for both dietary groups regarding progression of BMEP (63). Of note, this previous study was performed over a much shorter period, which may explain the lack of differences between cartilage thickness and volume, as well as the denuded area, between the groups with different weight loss methods.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, only participants in whom MR imaging could be performed were included in the OAI study; thus, participants who had issues with fitting into the MR imaging surgery). Yet, the only statistical trend found in the previous assessment of structural knee abnormalities and different types of weight loss (exercise, diet, and diet combined with exercise) was a beneficial effect for both dietary groups regarding progression of BMEP (63). Of note, this previous study was performed over a much shorter period, which may explain the lack of differences between cartilage thickness and volume, as well as the denuded area, between the groups with different weight loss methods.…”
Section: Discussionmentioning
confidence: 67%
“…While a recent study by Hunter et al with similar numbers of patients 45 , did not observe an association between weight loss and cartilage changes on MRI, the authors found a trend towards improvements in bone marrow lesions (BMLs). Given the association with BMLs and pain 46 , this may be of particular clinical relevance.…”
Section: Discussionmentioning
confidence: 89%
“…The diet only group also exhibited a significant decrease in knee compressive forces. Despite these improvements, there were no significant differences in changes in knee joint structural outcomes, including radiographic joint space narrowing and, in a subset of participants, MRI measures 6 .…”
Section: Introductionmentioning
confidence: 81%
“…The 6- and 18-month samples were collected at least 24 hours after the last acute bout of exercise training and sampling was postponed (1–2 weeks after recovery from symptoms) in the event of an acute respiratory, urinary tract, or other infection. Bilateral, posteroanterior, weight-bearing, knee x-rays were obtained with the participants’ knees flexed at 15 degrees using a positioning device (Synaflexer) as described 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation